Hemochromatosis in a β‐thalassemia minor patient with H63D homozygous mutation: A case report - Pokhrel, Nishan Babu (Clin Case Rep, 2020)
β‐thalassemia heterozygosity can cause significant iron overload when accompanied by HFE gene mutations and inappropriate iron supplementation.